Garap Rujak-rujakan dalam Sindhenan Gaya Surakarta - Suyoto Suyoto (Institut Seni Indonesia Yogyakarta, 2020)
ABSTRACTThis research reveals of garap rujak-rujakan in the Surakarta style sindhènan. Some issues to be explored in this reasearch are related to the garap rujak-rujakan, how to interpret balungan rujak-rujakan, and the function of rujak-rujakan in Surakarta-style sindhènan. These point are explained based on data on the presentation of musical instrument as a factual data exploration media. Data collection was carried out by means of literature studies, interviews, and also as a participant observer.The data collection was carried out by literature study, interviews, and also as a participant observer. The analysis is carried out by reinterpreting the thoughts and experience of the pengrawit through pragmatic reality. The interpretation uses interpretation method and garap analysis. The explanation and getting conclusions are carried out by the inductive method.The results obtained are that the rujak-rujakan is included in the shredded category which has a complementary and varied function. There are four types of rujak-rujakan models, namely rujak-rujakan with a descending melody, rujak-rujakan with an upward melody, rujak-rujakan with kempyung melody sèlèh, and rujak-rujakan with flat tones. Céngkok rujak-rujakan can be applied to melody compositions that reflect the core of the rujak-rujakan melody. So if there is a balungan melody that reflects the melody rujak-rujakan, then a pesindhèn can fill the balungan with céngkok rujak-rujakan. Rujak-rujakan is facultative, but its presence gives color or variety to the sindhènan.